17 x 63 + 37 x 17 =
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1a) -54 . 76 + 12 .(-76) + 76.(-34)
= (-54 - 12 - 34).76
= -100 . 76
= -176
b) 37.(63 - 24) - 63.(24 + 37)
= 37 . 63 - 37 . 24 - 63.24 - 63 . 37
= (37.63 - 63.37) - (37 + 63) . 24
= 0 - 100 . 24
= - 2400
2a) x + (-27) = -23 - x
=> x + x = -23 + 27
=> 2x = 4
=> x = 4 : 2
=> x = 2
b) xy + 2x - y = 15
=> x(y + 2) - y = 15
=> x(y + 2) - (y + 2) = 13
=> (x - 1)(y + 2) = 13 = 1 . 13 = 13 . 1
Lập bảng :
x - 1 | 1 | -1 | 13 | -13 |
y + 2 | 13 | -13 | 1 | -1 |
x | 2 | 0 | 14 | -12 |
y | 11 | -15 | -1 | -3 |
Vậy ...
x - 17 = 2 x 17 x 5
=> X - 17 = 170
=> x = 187
49 - x = 21 x 63 + 37 x 3 x 7
=> 49 - x = 21( 63 + 37)
=> 49 - x = 2100
=> x = - 2051
2x + 3x = 15
=> 5x = 15
=> x = 3
không ghi lại đề nha !
a ) = 2008 x ( 99 + 1 )
= 2008 x 100
= 200800
b ) = ( 490 - 390 ) x 365
= 100 x 365
= 36500
c) = 2364 x ( 37 + 63 )
= 2364 x 100
= 236400
d ) = 12345 x ( 17 + 23 + 1 + 35 + 24 )
= 12345 x 100
= 1234500
\(\dfrac{21}{11}\times\dfrac{22}{17}\times\dfrac{68}{63}\) = \(\dfrac{42}{17}\times\dfrac{68}{63}\) = \(\dfrac{8}{3}\)
Vì \(\dfrac{21}{11}\times\dfrac{22}{17}=\dfrac{21\times22}{11\times17}=\dfrac{42}{17}\)
Vậy:
\(\dfrac{21}{11}\times\dfrac{22}{17}\times\dfrac{63}{68}\) =\(\dfrac{42}{17}\times\dfrac{68}{63}\) =\(\dfrac{21\times2\times17\times4}{17\times21\times3}\) =\(\dfrac{8}{3}\) =
d) Ta có: \(32\%-0.25:x=-\dfrac{17}{5}\)
\(\Leftrightarrow0.25:x=\dfrac{8}{25}+\dfrac{17}{5}=\dfrac{93}{25}\)
hay \(x=\dfrac{25}{372}\)
Vậy: \(x=\dfrac{25}{372}\)
e) Ta có: \(\left(x+\dfrac{1}{5}\right)^2+\dfrac{17}{25}=\dfrac{26}{25}\)
\(\Leftrightarrow\left(x+\dfrac{1}{5}\right)^2=\dfrac{9}{25}\)
\(\Leftrightarrow\left[{}\begin{matrix}x+\dfrac{1}{5}=\dfrac{3}{5}\\x+\dfrac{1}{5}=-\dfrac{3}{5}\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{2}{5}\\x=-\dfrac{4}{5}\end{matrix}\right.\)
Vậy: \(x\in\left\{\dfrac{2}{5};-\dfrac{4}{5}\right\}\)
f) Ta có: \(-\dfrac{32}{27}-\left(3x-\dfrac{7}{9}\right)^3=-\dfrac{24}{27}\)
\(\Leftrightarrow\left(3x-\dfrac{7}{9}\right)^3=\dfrac{-8}{27}\)
\(\Leftrightarrow3x-\dfrac{7}{9}=-\dfrac{2}{3}\)
\(\Leftrightarrow3x=\dfrac{1}{9}\)
hay \(x=\dfrac{1}{27}\)
g) Ta có: \(60\%\cdot x+0.4x+x:3=2\)
\(\Leftrightarrow\dfrac{4}{3}x=2\)
hay \(x=\dfrac{3}{2}\)
Vậy: \(x=\dfrac{3}{2}\)
h) PT \(\Leftrightarrow\left|\dfrac{20}{9}-x\right|=\dfrac{2}{9}\) \(\Rightarrow\left[{}\begin{matrix}\dfrac{20}{9}-x=\dfrac{2}{9}\\x-\dfrac{20}{9}=\dfrac{2}{9}\end{matrix}\right.\) \(\Leftrightarrow\left[{}\begin{matrix}x=2\\x=\dfrac{22}{9}\end{matrix}\right.\)
Vậy ...
i) PT \(\Leftrightarrow\dfrac{8}{5}+\dfrac{2}{5}x=\dfrac{16}{5}\) \(\Leftrightarrow\dfrac{2}{5}x=\dfrac{8}{5}\) \(\Leftrightarrow x=4\)
Vậy ...
a) (37 - 17) . (-5) + 23 . (-13 - 17)
= 20 . (-5) + 23 . (-30)
= (-100) + (-690)
= -790
b) 63 . ( - 25 ) + 25 . (-23)
= (-63) . 25 + 25 . (-23)
= 25[(-63) + (-23)]
= 25 . (-86)
= -2150
= 17 X ( 63+37)
= 17 X 100=1700
NHỚ K NHÉ
\(17\cdot63+37\cdot17\)
\(=17\cdot(63+37)\)
\(=17\cdot100=1700\)